THE OWN STRESSES INFLUENCE ON SCALE EFFECT IN CONCRETE - Fenko, Aleksey; Yurko, Ilona; Hasenko, Anton; Krupchenko, Oleksandr; Yurko, Pavlo (Academic journal Industrial Machine Building Civil Engineering, 2019)
The experimental technique and the experiment results on the influence of own stresses unevenly distributed over cross section on materials strength and on scale effect are presented. The reasons for the occurrence and distribution of such influence are analyzed. Based on the experiments results on fragile duralumin samples, the inevitability of influencing on scale effect in concrete during compression stresses, which are caused by unevenly shrinkage over cross section was proved. Possible reasons for the different (sometimes opposing) results of experimental studies of various authors on scale effect in concrete in compression are explained. The influence of own stresses unevenly distributed over cross section on scale effect in concrete during compression, depending on samples size and concrete age, is analyzed in detail